Antibacterial activity of aqueous extract of propolis from Irapuato, Guanajuato, Mexico. - Bucio-Villalobos, Carlos Manuel (2016)
The objective of this study was to evaluate the antibacterial activity of an aqueous extract of propolis. In February 2015, the propolis was collected in an apiary located in Irapuato, Guanajuato, Mexico. 300 g of propolis were fractionated and added to 500 ml of an ethanol solution 70%, in continuous stirring for fteen days. The liquid phase was separated by vacuum ltration, the ethanol of that phase was evaporated in a rotoevaporator driven at 90 revolutions per minute (rpm) and 80 °C. The final residue was resuspended in distilled water, thereby obtaining the aqueous extract. A propolis extract obtained with concentrated ethanol was used as a reference control, in addition, ethanol and water controls were included. The antibacterial activity of the extracts was evaluated by diffusion technique in agar, using strains of Escherichia coli (ATCC-10536), Salmonella typhimurium (ATCC-13311), Listeria monocytogenes (ATCC-19115) and Staphylococcus aureus (ATCC-11632) developed in Tryptic-Soy-Agar. After be incubated the bacteria at 37 °C for 24 hours (h), and the halo of inhibition was measured. Only in the ethanol extract used as a control, was observed antimicrobial activity against S. aureus and L. monocytogenes; for E. coli and S. typhimurium was not observed any effect. The aqueous extract had no effect on any of the four bacteria evaluated, concluding that the active ingredients of propolis are not soluble in water, so are lost in a process of aqueous extraction.